Enhancing the support-execution model of strategy execution: A moderated mediation effect of strategy engagement and strategy communication - Chuah, Chin Wei; Teoh, Kenny; Abdullah, Haim Hilman (2015)
Strategy execution, a term that is commonly associated as the subsequent process of strategic planning (Bourgeois & Brodwin, 1984; Cater & Pucko, 2010) is now widely regarded as the most important problem in the field of strategic management (Speculand, 2009).Recent statistics shown that the success rate for strategy execution stands between 10% to 30% (Farsight Leadership Organization, 2007; Raps, 2004).Such poor success rate of strategy execution indicates that there is much to be explored about strategy execution. The effort to better understand strategy execution, however, is not without hurdles.Okumus & Roper (1999) postulate that one of the few reasons prohibiting the clear understanding of strategy execution is due to the different views and perceptions on strategy execution.Scholars from different disciplines are said to have different views and perceptions in conceptualizing strategy execution in their respective areas.Given the aforementioned hurdles in conceptualizing strategy execution, it is not surprising to see that there has been a period of paucity in researching strategy execution. Nonetheless, recent arising awareness on the importance of strategy execution as well as issues surrounding it in the practicing world, has once again, result in strategy execution becoming the center of strategic management scholar’s research attention. There has been consensus among strategic management scholars that strategy execution is now under-researched (Creasap, 2011; Crittenden & Crittenden, 2008; Gottschalk, 2008; Yang, Sun, & Martin, 2010) and much needs to be done to better understand strategy execution because poor strategy execution weakens subsequent strategic planning efforts (Crittenden & Crittenden, 2008).This study sets to answer call for more research on strategy execution by revisiting the support-execution model of strategy execution. Building on prior literature, this study introduces a new concept: “strategy engagement” as a mechanism to better explain the support-execution relationship. Rendering the concept of “engagement” as well as theory of engagement (Kahn, 1990, 1992), this study remodeled the support execution model such that strategy engagement is now a construct that intervene the relationship between organizational support and strategy execution.In addition to that, this study also examines the effect of strategy communication on the integrated model of strategy execution. On the basis of Craig (1999) communication theory, we argue that communication plays a role in strategy execution such that when communication is high and frequent, managers executing a strategy would perform better. Following through, a moderated mediation model which jointly examines the mediating role of strategy engagement and the moderating role of strategy communication were developed to facilitate this study.